AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN INOVATIF DI ERA REVOLUSI INDUSTRI 4.0 - Yeka Hendriyani; Hansi Effendi; Dony Novaliendry; Hastria Effendi (Jurnal Teknologi Informasi dan Pendidikan, 2019)
The main purpose of this paper is to uncover the results of a survey study regarding teacher opinions on the use of Augmented Reality (AR) in learning. For this purpose, marker-based cellular augmented reality applications have been developed and computer hardware is used as training material. In addition, teachers are given training for four days to get to know the basics of augmented reality technology, the software used, the environment to create marker-based AR objects. The data was collected through surveys and open-ended questions on teachers who are members of the English MGMP Kab. 50 cities. The tools and technology needed to develop AR and development experience are also shared. According to the survey results teachers are very enthusiastic about using augmented reality in their learning. The result of this article is the perception of the use of Augmented Reality technology for the development of instructional media by English teachers in the positive category.